Early and late stages of Developmental Biology in Argentina - Sanchez, Sara Serafina del V. (2021)
The history of science in Argentina is based on the enormous contribution that the great immigration of the 19th and 20th centuries produced in the country. The scientific and philosophical ideas and the role played especially by Italian scientists who arrived in the country produced a great impact on the different disciplines including Development Biology in emerging universities. The University of Tucumán pioneered the study of experimental biology, making important contributions to reproductive biology and to the early development of amphibians. The contribution of the Italian embryologist Armando Pisanó and the Argentinian Francisco D. Barbieri expanded the field to other universities and research centers located in Córdoba, La Plata, Bahía Blanca and Rosario. Given its strategic position, laboratories located in the city of Buenos Aires reached technological advances faster than others. Indeed, these laboratories saw the evolution from experimental biology to developmental genetics, renewing interest in this area. Currently, Developmental Biology brings together young researchers eager to consolidate regional and global collaboration networks that seek to help solve specific problems such as fertility, epigenetics, stem cells and tissue engineering.